2009
DOI: 10.1021/ja9045108
|View full text |Cite
|
Sign up to set email alerts
|

Mediated Electrochemical Oxidation of a Fully Encapsulated Redox Active Center

Abstract: While the direct electrochemical oxidation of ferrocene encapsulated inside a dimeric molecular capsule is essentially suppressed, a cationic ferrocene derivative binds to the capsule's external surface and acts as an effective electrochemical mediator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Reactions mediated by supramolecularly encapsulated transition metal complexes are rare,13 as cavities large enough to encapsulate the transition structure are required. Natural proteins,4, 5 and hydrogen‐bonded,6, 7 metal‐mediated,8, 9 or hydrophobically driven10, 11 synthetic multimolecular assemblies provide such spaces. For example, Raymond, Bergman et al.…”
Section: Methodsmentioning
confidence: 99%
“…Reactions mediated by supramolecularly encapsulated transition metal complexes are rare,13 as cavities large enough to encapsulate the transition structure are required. Natural proteins,4, 5 and hydrogen‐bonded,6, 7 metal‐mediated,8, 9 or hydrophobically driven10, 11 synthetic multimolecular assemblies provide such spaces. For example, Raymond, Bergman et al.…”
Section: Methodsmentioning
confidence: 99%
“…In an interesting extension to this study, Kaifer and colleagues recently revealed that suitable charged guests on the outside of the capsule can mediate electrochemical oxidation of encapsulated ferrocene. 153 As just discussed, encapsulated ferrocene is electrochemically silent, but when cationic ferrocene 52 + was added to a solution of the 44 2 -ferrocene complex the cationic guest became associated with the outside of the capsule. In contrast to the binding of viologen, only one cationic guest was observed to bind.…”
Section: Systems Utilizing the Hydrophobic Effectmentioning
confidence: 96%
“…150,151 Within this family, host 44-the so-called ''octaacid''-has proven to be particularly useful with at least six research groups independently exploring the unusual properties of the nano-capsule that results from its dimerization. 33,[152][153][154][155][156][157][158][159][160] Although the octaacid 44 is the most studied, it is relatively straightforward to change the outer coating of the cavitand. To take a structurally extreme example, Gibb and Grayson have reported on the synthesis of G3 dendritic cavitand 45, the first neutral, water-soluble, self-assembling host.…”
Section: Systems Utilizing the Hydrophobic Effectmentioning
confidence: 99%
“…We have utilized these carboxylate-functionalized capsules as nano-scale reaction flasks for photochemical reactions, [26][27][28][29][30][31] as a means to trapping excited states (excimers), 32 as a tool for the separation of hydrocarbon gases, 33 and as way to control the redox chemistry of encapsulated guests. 34 Indeed, the ability of these capsules to define a dry nano-environment in aqueous solution has resulted in others 35,36 independently utilizing the capsule for a variety of different purposes. Building on this work, the Gibb group has more recently been actively seeking new ways to functionalize the surface or coat of these cavitands to afford water solubility at physiological pH and biocompatibility in vivo.…”
Section: Qualities Of ''High-definition'' Supramolecular Drug Conjugatesmentioning
confidence: 99%